Numerical Simulation of 3D Multi-fluid Flows - SOUSA, F.S.; MANGIAVACCHI, N.; CASTELO, A.; NONATO, L.G.; TOMÉ, M.F. (Trends in Computational and Applied Mathematics, 2002)
A method to simulate three-dimensional unsteady multi-fluid flows with free surfaces is described. A sharp interface separates incompressible fluids of different density and viscosity. Surface and interface tensions are also considered and the required curvature is approximated at the fronts by a methodology described in [3]. The method is based on the GENSMAC [14] front-tracking method. The velocity field is computed using a finite-difference scheme in an Eulerian grid. The free-surface and the interfaces are represented by an unstructured Lagrangian grid. The method was validated comparing the numerical results with analytical results for a number of simple problems. Other more complex numerical simulations show the robustness of the method, and some comparisons with experimental results are also presented.